Reflections on Digital Image in Contemporary Times - Mortensen Steagall, M (UFSCar, 2021)
The image is carried out with a plurality of technological means and its representative growth has become a special advance in technology in recent years, which has allowed the production and transmission of data in a dynamic, sophisticated and increasingly accessible way. This article offers an understanding of the growing importance of image and its integration with technology, for the production and transmission of messages through a process that attempts to locate this development as an aspect linked to contemporary and understood by the mediations between the ways of seeing, as well. images and technical images.
Keywords: Technical images; Photographic Image; Ways of Seeing; Digital Image; Image technology